A Reconfigurable Phase-Shifted Full-Bridge DC–DC Converter with Wide Range Output Voltage - Benites Quispe, Jhon Brajhan [UNESP]; Mezaroba, Marcello; Batschauer, Alessandro Luiz; de Souza Ribeiro, Jean Marcos [UNESP] (MDPI, 2024)
This paper analyzes, designs and implements a reconfigurable phase-shifted full-bridge (PSFB) converter. It adopts the topology of the traditional PSFB converter and incorporates clamping circuits to solve some fundamental problems of conventional topology. In addition, auxiliary switches are employed for output reconfiguration, which allows expanding the output voltage range without compromising the system efficiency. Single pole double throw (SPDT) mechanical switches are used to realize series and parallel connections. In this paper, the characterization of the PSFB converter with clamping circuit and its design considerations are discussed. A 10 kW prototype with a power density of 0.485 W/cm3, 900 V input voltage and 400/800 V nominal output voltage was manufactured. The experimental results validated the analysis and confirmed the high conversion efficiency for a wide load range; an efficiency of 96.69% was obtained for the full load condition.
Keywords: phase-shifted full-bridge converter; reconfiguration; wide voltage range